Cairo: Mapping the neoliberal city in literature - Gewily, Nesma (AUC Knowledge Fountain, 2018)

(untitled)
While many scholars have explained neoliberalism and its impact on the economic, political and social spheres, writers have successfully grasped the everyday realities created by the implementation of the neoliberal policies. In my thesis, I am going to use literary maps to analyze three novels written by Egyptian writers at different stages of the neoliberal project. The novels are: Malik al-haÌ'zin (1983) (The Heron, 2005) by Ibrahim Aslan, An takun 'Abbas al-Abd (2003) (Being Abbas El Abd, 2009) by Ahmed Alaidiy and Yutubiya (2008) (Utopia, 2011) by Ahmed Khaled Towfik. Mapping the three novels demonstrate the changes that the city of Cairo and its inhabitants have undergone in the neoliberal era.